KEUNGGULAN POTENSI KEMIRI DAN KENARI TIDAK DIMANFAATKAN SECARA BAIK DI DESA PROBUR - Selfius Kolihar; Yosin E. Djolelang; Petrus Mau Telu Dony; Yermia S. Wabang (Adiba Aisha Amira, 2026)
This study aims to describe the utilization of candlenut and walnut potential and to identify the constraints and opportunities for their development in Probur Village, Alor Barat Daya District, Alor Regency. Probur Village has abundant natural resources, particularly candlenut and walnut commodities with high economic value; however, their utilization remains suboptimal. The community still manages these commodities traditionally, with limited knowledge, processing technology, and market access. This research employs a qualitative descriptive method, with data collected through observations and interviews with the Village Head and Village Secretary of Probur. The findings indicate that candlenut and walnut resources are abundant and have strong potential as sustainable income sources for the community. Nevertheless, limited processing skills, lack of technology, and insufficient assistance result in these commodities being sold mainly in raw form, generating low added value. The study concludes that the development of candlenut and walnut potential in Probur Village requires community capacity building, the introduction of appropriate processing technologies, and sustainable marketing support to improve rural economic welfare.